Nature of the Mind : an Introduction. - Carruthers, Peter, 1952- (Taylor & Francis, 2003)
The Nature of the Mind is a comprehensive and lucid introduction to the major themes in philosophy of mind. It carefully explores the conflicting positions that have arisen within the debate and locates the arguments within their context.